Effects of Injector Spray Angle on Performance of an Opposed-Piston Free-Piston Engine - Qinglin Zhang; Zhaoping Xu; Shuangshuang Liu; Liang Liu (Energies, 2020)
A free-piston engine is a novel internal combustion engine which has the advantages of a variable compression ratio and multi-fuel adaptability. This paper focuses on numerical simulation for combustion process and spray angle optimization of an opposed-piston free-piston engine. The working principle and spray-guided central combustor structure of the engine are discussed. A three-dimensional computational fluid dynamic model with moving mesh is presented based on the tested piston motion of the prototype. Calculation conditions, spray models, and combustion models were set-up according to the same prototype. The effects of spray angle on fuel evaporation rate, mixture distribution, heat release rate, in-cylinder pressure, in-cylinder temperature, and emissions were simulated and analyzed in detail. The research results indicate that the performance of the engine was very sensitive to the spray angle. The combustion efficiency and the indicated thermal efficiencies of 97.5% and 39.7% were obtained as the spray angle reached 40°.